Gender Perspective in Medical Specializations in Uruguay: Does Gender Influence the Choice of General Surgery? - Wagner , Gabriela; Campos , Maite; Machin , Mariella; Cerchiari , Emilia; Mazzola , Graciela; Rodríguez, Gabriela; Boudrandi, Sonia (Cirugía del Uruguay, 2025)
The significant increase in women's enrollment in tertiary and university programs is also evident in the field of Medicine. The marked feminization of medical school enrollment and graduation has led to a shift in specialty choices when examined from a gender perspective. Nevertheless, a woman’s decision to pursue a surgical specialty continues to elicit a degree of skepticism, and disparities remain in the proportion of men and women entering surgical fields. This difference—multifactorial and often unconscious—contributes to the underrepresentation of women in academic surgery and in higher-ranking positions. International literature consistently highlights this reality across the globe; however, there is limited research published on this issue in our country. This study analyzes the situation in Uruguay regarding the presence of women in medical and surgical specialties, with a particular focus on general surgery. We conducted a descriptive study of the current status of women in Medicine in Uruguay, both overall and within specific specialties. Our primary focus is the current situation of women in the field of general surgery. We used data provided by the General Planning Office of the University of the Republic, based on available records from 2009 to 2022. Specifically, we examined the role of women in academic teaching within General Surgery, using data from the active faculty registry of the UDELAR School of Medicine, categorized by academic rank as of December 2024.